Ethical leadership: A structured review into construct, measurement, public sector context and effects. Issue 1 (24th December 2019) - Shakeel, Fahad; Kruyen, Peter Mathieu; Van Thiel, Sandra
Abstract : Purpose: The purpose of this paper is to offer a review of the selected literature in ethical leadership synthesizing findings from 45 articles selected from journals on leadership, public administration, organizational behavior, psychology and ethics. Design/methodology/approach: Four themes are addressed: the conceptualization of ethical leadership theories, the existence of popular measurement instruments for ethical leadership, findings on ethical leadership in the public sector and outcomes of ethical leadership in terms of benefits and negative consequences. Findings: The definition by Brown et al. (2005) is the most frequently used definition, even though recent criticism states that this definition may be too narrow. Ethical leadership is usually measured by means of a survey; however, there are at least three different questionnaires in use. In the public sector, ethical leadership has been linked to both positive outcomes and negative consequences. Research limitations/implications: This paper only includes selected academic articles and does not include published books. Originality/value: Based on our findings, the authors present recommendations for future research, among others into a broader conceptualization of ethical leadership and the use of mixed methods.